A Stable Core–Shell Si@SiOx/C Anode Produced via the Spray and Pyrolysis Method for Lithium-Ion Batteries - Li, Xuelei; Zhang, Wenbo; Wang, Xiaohu; Teng, Wanming; Nan, Ding; Dong, Junhui; Bai, Liang; Liu, Jun (Frontiers in Chemistry, 2022)
In the serious situation of energy shortage and environmental problems, Si has been regarded as one of the most potential anode materials for the next generation lithium-ion batteries as a result of the relatively low delithiation potential and the eminent specific capacity. However, Si anode is subjected to the huge volume expansion-contraction in the charging-discharging process, which can touch off pulverization of the bulk particles and worsens the cycle life. Herein, to reduce the volume change and improve the electrochemical performance, a novel Si@SiOx/C anode with core-shell structure is designed by spray and pyrolysis methods. The SiOx/C shell not only ensures the structure stability and proves the high electrical conductivity, but also prevents the penetration of electrolyte, so as to avoid the repetitive decomposition of electrolyte on the surface of Si particle. As expected, Si@SiOx/C anode maintains the excellent discharge capacity of 1333 mAh g−1 after 100 cycles at a current density of 100 mA g−1. Even if the current density reaches up to 2000 mA g−1, the capacity can still be maintained at 1173 mAh g−1. This work paves an effective way to develop Si-based anodes for high energy density lithium-ion batteries.